Nuclear Deformation During Neutrophil Migration at Sites of Inflammation - Salvermoser, Melanie; Begandt, Daniela; Alon, Ronen; Walzog, Barbara (Frontiers in Immunology, 2018)
Cell migration is indispensable for various biological processes including angiogenesis, wound healing and immunity. In general, there are two different migration modes described, the mesenchymal migration mode and the amoeboid migration mode. Neutrophils rapidly migrate towards the sites of injury, infection, and inflammation using the amoeboid migration mode which is characterized by cell polarization and a high migration velocity. During site directed trafficking of neutrophils from the blood stream into the inflamed tissue, neutrophils must first withstand shear stress while migrating on the 2-dimensional endothelial surface. Subsequently, they have to cross different physical barriers during the extravasation process including the squeezing through the compact endothelial monolayer that comprises the blood vessel, the underlining basement membrane and then the 3-dimensional meshwork of extracellular matrix (ECM) proteins in the tissue. Therefore, neutrophils have to rapidly switch between distinct migration modes such as intraluminal crawling, transmigration and interstitial migration to pass these different confinements and mechanical barriers. The nucleus is the largest and stiffest organelle in every cell and is therefore the key cellular element involved in cellular migration through variable confinements. This review highlights the importance of nuclear deformation during neutrophil crossing of such confinements, with a focus on transendothelial migration and interstitial migration. We discuss the key molecular components involved in the nuclear shape changes that underlie neutrophil motility and squeezing through cellular and ECM barriers. Understanding the precise molecular mechanisms that orchestrate these distinct neutrophil migration modes introduces an opportunity to develop new therapeutic concepts for controlling pathological neutrophil driven inflammation.